Hands‐on training based on quantifying radiant exposure improves how dental students cure composites: Skill retention at 2‐year follow‐up. (8th December 2020) - Balhaddad, Abdulrahman A.; Marghalani, Abdullah A.; Raderman, Michael A.; Miginsky, Elaine; Massey, Ward; Strassler, Howard; Anne Melo, Mary
Abstract: Introduction: The durability and longevity of composite restoration are much dependent on the accurate delivery of the energy required to polymerise the material. This study aimed to investigate the extent to which undergraduate dental students acquire and retain light‐curing skills following hands‐on training. Materials and Methods: Hands‐on training comprises faculty tutoring for critical aspects of the light‐curing procedure, such as distance and angulation of the light‐curing tip. Assessments of the students' ability to deliver a specified radiant exposure to class III and I simulated RBCs using a dental simulator (MARC‐PS ® ) at three different time points after the training. Data were analysed using repeated measure ANOVA. Results: Immediately after the training, students' performance on curing was improved ( p < .05). Overall, the radiant exposure increased after training, but the students lost some of the benefits with time. For curing in the anterior section (anterior sensor‐class III), the mean radiant exposure values increased by approximately 20% after the training. After 2 years, the values were 15% greater than baseline values. For curing in the posterior section (posterior sensor‐class I), the mean radiant exposure values increased by approximately 150% after the training. A significant decrease ( p < .05) was observed; however, the radiant exposure values were still 82% greater than the baseline after 2 years. Conclusion: A hands‐on training dedicated to light‐curing procedures facilitated acquisition and retention up to a 2‐year follow‐up of skill on how light cure composite inside the mouth. The training was more relevant for curing in posterior areas, where orientation can significantly impact light‐curing. A hands‐on training where the radiant exposure can be measure gave objective measurement metrics to guide the curing performance. This approach is an effective means of teaching practical skills to dental students.